A Relative Cost of Control Analysis of Once-Weekly Semaglutide Versus Exenatide Extended-Release and Dulaglutide for Bringing Patients to HbA1c and Weight Loss Treatment Targets in the USA - Johansen, Pierre (Adv Ther, 2019)
INTRODUCTION: The SUSTAIN 3 and 7 clinical trials compared the efficacy and safety of once-weekly semaglutide relative to exenatide extended-release (ER) and dulaglutide, respectively, in the treatment of patients with type 2 diabetes (T2D). The trials included a series of clinically relevant single and composite endpoints focused on improving glycemic control and reducing body weight, while avoiding hypoglycemia. The present study combined SUSTAIN 3 and 7 outcomes with short-term treatment costs to evaluate the relative cost of control of once-weekly semaglutide versus exenatide ER and dulaglutide. METHODS: Proportions of patients reaching three endpoints were taken from SUSTAIN 3 and 7 for comparisons with exenatide ER and dulaglutide, respectively. The endpoints investigated were HbA1c < 7.0%, HbA1c < 7.0% without hypoglycemia or weight gain, and a ≥ 1.0% HbA1c reduction with ≥ 5.0% weight loss. Annual per patient treatment costs were based on US wholesale acquisition costs from July 2018. Relative cost of control was calculated by plotting the ratio of the treatment costs and the ratio of the proportions of patients reaching each endpoint on the cost–efficacy plane. RESULTS: Once-weekly semaglutide 0.5 mg and 1.0 mg were most effective at bringing patients to each of the three endpoints across both SUSTAIN trials. The efficacy-to-cost ratios for once-weekly semaglutide 0.5 mg and 1.0 mg were also superior to all comparators when assessing both the single endpoint of HbA1c < 7.0% and the two composite endpoints including weight loss and hypoglycemia. CONCLUSIONS: The present study showed that once-weekly semaglutide 0.5 mg and 1.0 mg offer superior cost of control versus exenatide ER and dulaglutide in terms of achieving single and composite endpoints, based on an analysis of retrieved dropout data. Once-weekly semaglutide 0.5 mg and 1.0 mg would therefore represent good value for money in the USA, particularly in the attainment of multi-model T2D treatment goals. FUNDING: Novo Nordisk A/S.